Penentuan Penerima Bantuan Rumah Tidak Layak Huni Menggunakan Metode Simple Additive Weghting - Sonia Ratnaning Pertiwi; Yustina Retno Wahyu Utami; Sri Harjanto (STMIK Sinar Nusantara, 2021)
Uninhabitable Housing Assistance (RTLH) is a government program which distribute to village office, it has purpose to improve the life quality of community. Poor people can life convenient with Uninhibitable Houses Assistence. Determination of social assistence construction of Uninhabitable Houses is going to do by relying on the intitution. The purpose of this research is creating a decision support system that can help to determine the appropriate poor people are receiving social assistence of Uninhabitable House (RTLH) using simple additive weighting (SAW) method. It is used the creteria such as, the monthly income, the occupation, the total of burden, the condition of house wall, the condition of house floor, the condition of house roof, and the condition of bathroom. The result of this research is the beneficial system for receiver of Uninhabitable Houses.